Technology-Enhanced Action Research Training for Science Teachers: An Explanatory Sequential Mixed-Methods Needs Assessment - Walag, Angelo Mark P; Madronero, Jason M; Tapay, Alyana Grace Q; Sales, Glea Mae G; Malawi, Naurah M (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aimed to determine the training needs of science teachers in conducting action research and to examine the relationship between their prior research experience and confidence in performing research-related tasks. Methodology: An explanatory sequential mixed-methods design was used. Data were collected through a validated online survey of 24 science teachers in Cagayan de Oro City, Philippines, followed by semi-structured interviews with eight participants. Data were analyzed using descriptive statistics, Spearman’s rho correlation, and thematic analysis to examine teachers’ perceptions of digital tools and technology-enabled support in enhancing action research competence. Main Findings: Teachers showed high confidence in identifying research problems but low confidence in technical areas such as data analysis and research writing stages where digital tools could offer substantial support. Prior research experience significantly correlated with confidence in data analysis (ρ = 0.439, p < 0.05). Qualitative findings highlighted barriers such as limited mentoring, time constraints, and lack of institutional structures to support technology based research training. Teachers expressed strong interest in technology enhanced mentoring, online analytics workshops, and digital writing support tools. Novelty/Originality of this study: This study contributes a novel sequential explanatory framework for diagnosing science teachers’ research competencies while integrating technological considerations into professional development design. Unlike prior assessments relying solely on traditional surveys, this study foregrounds how digital platforms, online mentoring, and technology enhanced training models can address persistent skill gaps. The findings offer actionable insights for designing innovative, technology supported research capacity-building programs for science teachers.